Peripheral cranio-spinal nerve communication for trapezius muscle control using axonal profiling through immunostaining - Miri Kim; In-Seung Yeo; Tae-Hyeon Cho; Ju-Eun Hong; Shin Hyung Kim; Hun-Mu Yang (Scientific Reports)
Abstract Accessory nerve (CNXI) has been known to be the primary conduit for motor control of the trapezius, while the supplementary cervical nerves (C3 and C4) are responsible for processing sensory information from muscle. However, the lack of substantial direct evidence has led to these conclusions being regarded as mere speculation. This study used immunostaining (using antibodies against neurofilament 200 for all axons, choline acetyltransferase for cholinergic axons, tyrosine hydroxylase for sympathetic axons, and alpha 3 sodium potassium ATPase for proprioceptive afferent axons) of human samples to verify the functional contributions of nerves. Study highlights the pivotal role of C3 and C4 in regulating precise movements of trapezius, contributing to motor control, proprioceptive feedback, and sympathetic modulation. CNXI is composed primarily of somatic efferent fibers, with significant numbers of sympathetic or sensory fibers. Furthermore, C3-4 have both cholinergic and non-cholinergic axons, suggesting their involvement in proprioceptive feedback and somatic efferent functions. Although less common, mechanosensors such as nociceptive sensor and sympathetic fibers are also supplied by these cervical nerves. The study demonstrated that these nerves contain motor fibers and significant proprioceptive and sympathetic axons, challenging the long-held notion that CNXI are motor and upper spinal nerves are sensory.